Diagnostic Dilemma in Psychiatry: Disease of the Mind or the Media?. (April 2022) - Syed, Shahan; Robinson, Julianna; Reddington, Bridget
Abstract: Introduction: Delusions, such as belief in conspiracy theories (CT), exist on a continuum representing clinical and subclinical populations. Some individuals are more susceptible to CT belief. Social media has allowed conspiracy theories to spread relatively unchecked. We report a previously healthy male hospitalized for delusions and reckless behavior. We analyze potential risk factors affecting this patient. Case Presentation: A 54-year-old Caucasian male presents with worsening persecutory and grandiose delusions over the past 6 months. An active participant in conspiracy theory-related online forums, he believes he has sensitive information regarding the Federal Bureau of Investigation. He endorses delusions of surveillance and tracking by family members, citing these concerns prompted him to rely on public transportation and prepaid cell phones, and even trespassing on U.S. Navy property. On evaluation, the patient prompts the team to review his collection of classified evidence claiming government involvement in a global sex trafficking operation. When challenged, the patient becomes argumentative, citing social media sources. He shows no evidence of overt depression, mania, or post-traumatic stress. The patient's level of functioning is reduced but not markedly impaired and he maintains employment. CBC, CMP, noncontrast head CT, CXR, and EKG are unremarkable. Cannabinoids are found on UTOX. He has a Positive and Negative Syndrome Scale score of 23/49 (positive), 10/49 (negative), and 31/112 (General Psychopathology), and Brown Assessment of Beliefs Scale score of 19/24. Discussion: Conspiracy theories (CT) are the result of an altered perception of reality. Belief in CT correlates with negative social, health, and civic outcomes, including increased tolerance to violent and antisocial behavior. Magical thinking, trait Machiavellianism, narcissistic traits, and primary psychopathy have been shown to be significant positive predictors of belief in CT. Individuals with maladaptive perception/attribution styles may also develop cognitive distortions. Finally, intuitive thinking, as opposed to analytical thinking, is associated with CT beliefs. Social or political crises may incite elevated emotional responses, causing increased popularity of CT during times of major social or political change. Identifying these traits may be useful for clinicians providing interventions for patients with CT ideation. This patient's presentation with delusions and nonimpaired functioning may be explained by deficits in objective reasoning as a result of maladaptive cognitive and affective response mechanisms, rather than psychotic illness. Conclusion: Conspiracy theories are generated as a consequence of social and political discontent and can result in a clinically significant impact on mental health and well-being. Patients with narcissistic traits and primary psychopathy are more likely to demonstrate impaired judgment related to CT. Funding: No funding